Antioxidant capacity of betacyanins as radical scavengers for peroxyl radical and nitric oxide. (1st January 2015) - Taira, Junsei; Tsuchida, Eito; Katoh, Megumi C.; Uehara, Masatsugu; Ogi, Takayuki
Highlights: Antioxidant activity of betacyanins was examined by an ORAC assay and ESR technique. Betacyanins had a strong antioxidant capacity and directly scavenged NO. Betanidin with a catechol group had higher activity than those of the glycoside of betacyanins. Betacyanins will be useful as a natural pigment including physiological activity. Abstract: This study was designed to assess the antioxidant capacity of betacyanins as indole derived plant pigments, such as betanin, phyllocactin and betanidin. The antioxidant capacity of the betacyanins was evaluated as an index of radical scavenging ability using the peroxyl radical generating system in the presence of AAPH and NO generating system using NOR3 as an NO donor. The peroxyl radical scavenging capacity was dose-dependent in the low concentration range (25–100 nM). The mol-Trolox equivalent activity/mol compound (mol-TEA/mol-compound) as an index of the antioxidant capacity indicated the following order at 10.70 ± 0.01, 3.31 ± 0.14 and 2.83 ± 0.01 mol-TEA/mol-compound for betanidin, betanin and phyllocactin, respectively. In addition, betacyanins reduced the nitrite-level in the low concentration range of 2.5–20 μM. The IC50 values (μM) of nitrogen radical scavenging activity were 24.48, 17.51 and 6.81 for betanin, phyllocactin and betanidin. ESR studies provided evidence that the compounds directly scavenged NO. These results indicated that betacyanins have a strong antioxidant capacity, particularly betanidin with a catechol group had higher activity than those of the glycoside of betacyanins. This study demonstrated that the betacyanins will be useful as natural pigments to provide defence against oxidative stress.